PENGARUH PDB, JUMLAH PENDUDUK DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN PADA KAB/KOTA DI PROVINSI ACEH - Jannatun Nufus; Ratna Husein (JURNAL EKONOMIKA INDONESIA, 2021)
This study aims to determine the effects of GRDP, population, and HDI on poverty in 23 districts/cities in Aceh Province. This study uses secondary data obtained from the Central Bureau of Statistics during 2012-2018 and cross-section data from 23 districts/cities, thus forming a total panel data of 161 data. The data analysis method used is a panel data regression model using the Eviews 9 program. The results show that partially the GRDP and population do not have a significant and negative effect on poverty in districts/cities in Aceh Province. Meanwhile, HDI partially has a significant and negative effect on the poverty of districts/cities in Aceh Province. The magnitude of the influence of GRDP, total population, and HDI on poverty is 0.374 (37.4%), while those influenced by other variables outside this model are 0.626 (62.6%). Suggested: Local governments should increase sub-sector efforts to boost GDP, to reduce poverty levels.Keywords:Poverty, GRDP, Total Population, Human Development Indekx